Lacrimal and meibomian gland evaluation in dry eye disease: A mini-review - Swati Singh; Pragnya Rao Donthineni; Saumya Srivastav; Christina Jacobi; Sayan Basu; Friedrich Paulsen (Indian Journal of Ophthalmology, 2023)
Lacrimal and meibomian glands contribute to the aqueous and lipid components of tear film, respectively. Their evaluation remains central to diagnosing and managing dry eye disease (DED). The review discusses the differences and reliability of various diagnostic tests and commercially available devices used for DED diagnosis. Slit-lamp-based techniques are direct palpebral lobe and tear flow assessment, Schirmer test, meibum quality and expressibility, and evaluation of tear meniscus height. Non-invasive tear meniscus height (TMH), tear break-up time (TBUT), lipid layer thickness (LLT), and meibography are machine-based diagnostic tests. The structure–function correlation of the tear-producing glands gives more comprehensive details than either information alone. Many devices are available in the market, which make DED diagnosis an easy feat, but the tests should be interpreted keeping in mind the intra-observer and inter-observer repeatability. Also, the tear film displays a huge variability as per the environmental conditions and impact of blinking. Hence, the examiner should be well versed with the techniques and repeat the test two to three times to obtain an average reading, which is more reliable. The recommended sequence of tests for diagnosing DED is a dry eye questionnaire, TMH, LLT, NIBUT (FBUT if non-invasive test is unavailable but should be performed after osmolarity), tear osmolarity, meibography, and ocular surface staining. Invasive tests such as Schirmer should be performed after the non-invasive tear film diagnostic testing.